(3GdJPcQI GdMeOhfjIs - (3eMeO Hf GdMSf Hf eMeO Hf Ydj Hf MeOhf, CHh GdeYGdj, HgGA GdOjf GdHZOGOj,J (B562 (3g` s
(3ChdgG (B:s
(3ef GdLRA GdNGeS (B: (3HGH GdeQGKi hGdJYGRi , GdMeO dg GdNGdb GdHGYK GdQGRb GdhQGK GdPi bOQ GdMjGI hGdehJ ,hLYd dgeG CLdGde jNT ajg GdahJ hfbd Ndbg ef OGQ GdafGA Edi ebQ GdHbGA s
(3BNQgG (B:s
(3ef GdLRA GdSGOS (B: (3JMGhd Cf jbhe CHh RjGO hOhf bjGeg TjH GdZQGH CJJ HLhGHgG JcJGd ajg aQGMJ hgj aGQZI GdLQGH s
(3fSNI KGdKIs
(3hJTJed Ydi Chd GdHGH (B19s
(3hGdHGH (B27 (3Edi BNQ GdHGH (B29 (3ef GdLRA (B5 (3, (B6 (3ef GdcJGHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B85 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B217s
(3GdLRA (B1 - (3U (B383 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B163 s
Keywords: (3GdCOHs